A New Pattern for the Deployment of IT Governance Frameworks in Organizations - Yamami, Abir EL; Mansouri, Khalifa; Qbadou, Mohammed; Illoussamen, Elhossein (International Journal of Engineering and Technology, 2018)
The multiplicity of Information system frameworks problem has emerged as a strategic problem that involves a myriad of organizational and technical issues. This paper provides a new pattern to support IT governance framework selection in organizations, the aim is to overcome the problems of overlap, contradiction and redundancy between these frameworks. Yet, it proposes a practical approach formally developed according to Design Science Research approach, it addresses an area of relevance to both practitioners and academics and suggests solutions and tools that can help organizations to optimize their investment in the organizational transformation projects. In order to develop a synthesis, the proposed pattern has been applied in a Moroccan SME, the results show how the SME can rapidly cover maximal IT processes by deploying the proposed approach when adopting IT governance frameworks. It is found that the adoption of ITIL, Val-IT and PMBOK frameworks is sufficient to cover all the IT processes of this company.